Utility of item 9 of the patient health questionnaire in the prospective identification of adolescents at risk of suicide attempt. Issue 5 (31st July 2021) - Penfold, Robert B.; Whiteside, Ursula; Johnson, Eric E.; Stewart, Christine C.; Oliver, Malia M.; Shortreed, Susan M.; Beck, Arne; Coleman, Karen J.; Rossom, Rebecca C.; Lawrence, Jean M.; Simon, Gregory E.
ABSTRACT: Introduction: Previous studies report that item 9 of the Patient Health Questionnaire (PHQ9) is useful for stratifying risk of suicide attempt in adults. This study re‐produced the utility of item 9 of PHQ9 in assessing risk of suicide attempt in adolescents. Materials and Methods: Individuals aged 13 to 17 years in 4 health systems with a diagnosis of depression and history of treatment were included. We estimated time to first observed fatal or non‐fatal suicide attempt in the 2 years following completion of a PHQ9, stratified by response to item 9. Results: There were 51, 807 PHQ9 questionnaires for 20, 363 youth and 861 instances of suicide attempt. Cumulative probability of suicide attempt ranged from approximately 3.3% (95% CI, 3.0 to 3.5%) for those responding "not at all" on item 9 to 10.8% (95% CI, 9.2 to 12.4%) for those responding "nearly every day". These probabilities are more than 3 times higher than previously reported in adults. Conclusion: PHQ item 9 is useful for stratifying risk of suicide attempt in the 2 years following completion of the questionnaire. Monitoring PHQ item 9 over time for patients in treatment for depression can be useful for population health management of adolescents with depression.